Who suffered most? Parental stress and mental health during the COVID-19 pandemic in Germany; Wer leidet am stärksten? Erziehungsstress und psychische Belastungen bei Eltern während der COVID-19 Pandemie in Deutschland - Jianghong Li; Mareike Bünning; Till Kaiser; Lena Hipp (JFR – Journal of Family Research, 2022)
[Objective:] This study examines gender and socioeconomic inequalities in parental psychological wellbeing (parenting stress and psychological distress) during the COVID-19 pandemic in Germany [Background:] The dramatic shift of childcare and schooling responsibility from formal institutions to private households during the pandemic has put families under enormous stress and raised concerns about caregivers' health and wellbeing. Despite the overwhelming media attention to families' wellbeing, to date limited research has examined parenting stress and parental psychological distress during the COVID-19 pandemic, particularly in Germany. [Method:] We analyzed four waves of panel data (N= 1,771) from an opt-in online survey, which was conducted between March 2020 and April 2021. Multivariable OLS regressions were used to estimate variations in the pandemic's effects on parenting stress and psychological distress by various demographic and socioeconomic characteristics. [Results:] Overall, levels of parenting stress and psychological distress increased during the pandemic. During the first and third wave of the COVID-19 pandemic, mothers, parents with children younger than 11 years, parents with two or more children, parents working from home as well as parents with financial insecurity experienced higher parenting stress than other sociodemographic groups. Moreover, women, respondents with lower incomes, single parents, and parents with younger children experienced higher levels of psychological distress than other groups. [Conclusion:] Gender and socioeconomic inequalities in parents' psychological wellbeing increased among the study participants during the pandemic. – – [Fragestellung:] Diese Studie untersucht geschlechtsspezifische und sozioökonomische Ungleichheiten bei elterlichem Stress und psychischen Belastungen während der COVID-19 Pandemie in Deutschland [Hintergrund:] Zur Eindämmung der COVID-19 Pandemie wurde die Verantwortung für Kinderbetreuung und schulische Bildung von formellen Institutionen auf die Eltern verlagert, was diese mutmaßlich unter enormen Stress gesetzt und ihr psychisches Wohlbefinden beeinträchtigt hat. Obwohl medial ausführlich über die zusätzlichen Belastungen von Familien berichtet wurde, haben elterlicher Stress und psychische Belastungen während der Krise im Rahmen wissenschaftlicher Untersuchungen wenig Aufmerksamkeit erhalten. Das gilt insbesondere für Untersuchungen zu Deutschland. [Methode:] Die vorliegende Studie nutzt daher vier Wellen (N= 1.771) einer Opt-in-Panelbefragung, die zwischen März 2020 und April 2021 durchgeführt wurde. Mithilfe multivariabler OLS-Regressionen untersuchen wir die Auswirkungen der Pandemie auf elterlichen Stress und psychische Belastungen unter Einbeziehung einer Vielzahl demographischer und sozio-ökonomischer Merkmale. [Ergebnisse:] Insgesamt haben sich Stress und psychische Belastungen von Eltern durch die Pandemie erhöht. Während der 1. und 3. Pandemiewelle hatten Mütter sowie Eltern mit Kindern unter 11 Jahren, Eltern mit zwei und mehr Kindern, Eltern, die im Homeoffice arbeiteten, ebenso wie Eltern in finanziell prekären Lagen eine größere Verschlechterung bei Stress zu verzeichnen als andere soziodemografische Gruppen. Eine Verschlechterung bei psychischen Belastungen scheint es bei Frauen, Haushalten mit geringerem Einkommen, Alleinerziehenden und Eltern jüngerer Kinder gegeben zu haben. [Schlussfolgerung:] Die geschlechtsspezifischen und sozialen Ungleichheiten beim psychischen Wohlbefinden der Eltern nahmen bei den Studienteilnehmern während der Pandemie zu.
doi:10.7802/2122
Keywords: 300; COVID-19; parenting stress; gender inequality; mental health; psychological distress; Germany; children; Elternschaft; Stress; Geschlechterungleichheit; Kinder; psychische Gesundheit; psychische Belastung; Deutschland